Contextual violence and its link to social aggression: a study of community violence in Juárez - Martín del Campo Ríos, Jaime (2020)
The city of Juárez, Mexico has been immersed in an atmosphere of violence and danger for more than a decade. Due to this violence, residents of Juárez may be at risk of severe contextual victimization, which occurs when individuals are indirectly affected by the physical and socio-cultural conditions of their violent communities through second-hand information (e.g., witnessing or hearing about violent acts in their everyday life). The objective of this study was to explore the effects of contextual victimization on variables related to community violence such as aggression, post-traumatic stress disorder (PTSD), and acceptance of violence. Data were collected from a sample of university students in Juárez (n = 298) using the Aggression Questionnaire (AQ), the Acceptance of Violence Scale (AVS), Checklist for PTSD Traits scale, and the Contextual Victimization by Community Violence scale (CVCV). Participants’ responses were analyzed in structural equation models (SEM) to uncover the latent variables behind each scale and test the hypothesized effects of CVCV on PTSD, AQ and AVS. Good validity indexes and internal consistency of all instruments were confirmed. SEM show significant positive effects of contextual violence on PTSD and PTSD on the disposition to aggression, but not on the acceptance of violence. Also, the variance explained of PTSD and AQ found in the sample of women (20% of PTSD and 23% of AQ) is almost twice than in men’s sample (9% for PTSD and 14% for AQ).